Penerapan QR-Code Scanning Dalam Proses Absensi Siswa Dan Guru Berbasis Web Dengan Metode Agile - Fadel Yunus Mahrus; Entis Sutrisna (CV. Multi Kreasi Media, 2024)
This study aims to reduce the efficiency of the manual attendance system used at Sirajul Falah Vocational School by creating a web-based attendance system with a QR Code scanner. The research methods used include planning, data collection, system design, implementation, system testing, and report writing. The previous attendance system at SMK Sirajul Falah had deficiencies in efficiency and accuracy. In this study a web-based attendance system was implemented using a QR Code scanner to increase efficiency and accuracy in recording student and teacher attendance. The main findings of this study are that a web-based attendance system with a QR Code scanner can reduce fraud and increase the efficiency of the attendance process. This system allows students and teachers to record attendance quickly and accurately by scanning a unique QR Code. This research is expected to contribute to the development of a more efficient and accurate attendance system at Sirajul Falah Vocational School. With the existence of a web-based attendance system with a QR Code scanner, it is hoped that it can improve the management of student and teacher attendance and reduce errors and fraud in recording attendance.